Judge's Consideration of the Custody to a Husband (Research at the Syar'iȳah Tapaktuan Court) - Sufyan Ilyas (Budapest International Research and Critics University, 2019)
This research deals with Judge's Consideration of the Provision of Parental Rights to a Husband (Research at the Syar'iȳah Tapaktuan Court). This research used qualitative research approach that emphasizes quality in accordance with descriptive understanding. This research is in the form of an analysis of cases relating to consideration of the judge of the provision of custody of minors to their husbands. The findings show that the problem of custody of minors is given to the husband must prioritize the interests of the child. Not based on who is more entitled or not, but with a number of reasons that benefit the child. By putting forward psychological and psychological factors the child becomes the most important part for bagiakim in giving decisions on custody of minors. In the case of child care that must be considered solely the interests of the child and have the ability and ability to provide security to the child.